Xenophyophore-associated mitogenomes: genomic investigations of two specimens from the Clarion-Clipperton Zone - Gastineau, Romain; Mianowicz, Kamila; Dąbek, Przemysław; Otis, Christian; Lemieux, Claude; Turmel, Monique; Wawrzyniak-Wydrowska, Brygida; Stoyanova, Valcana; Krawcewicz, Artur; Wróbel, Rafał J.; Abramowski, Tomasz; Gooday, Andrew J. (Frontiers in Marine Science, 2025)
IntroductionXenophyophores are large benthic agglutinated Foraminifera that are a major component of the Clarion-Clipperton Zone megafauna.MethodsTwo xenophyophore specimens were obtained and submitted to genomic investigations.ResultsFor both specimens, it was possible to obtain a ca. 25 kb circular xenophyophore-associated mitochondrial genome (XAM) showing similar gene contents with other Retaria, with which they are associated by a maximum likelihood multiprotein phylogeny. One of the specimens yielded a complete cluster of nuclear rRNA genes, the first to be obtained from a xenophyophore. Another full cluster of rRNA, likely belonging to Endomyxa parasites, was found within both specimens.DiscussionAlthough the agglutinated nature of xenophyophores currently prevents a definitive conclusion, the mitogenomes obtained may represent the first to be obtained from those foraminifera. Deeper enquiries are required in order to properly ascribe these genomes to their host organism and to clarify the nature of the possibly parasitic Rhizaria associated with the xenophyophores.